2020
DOI: 10.3390/nu12103146
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Total Cysteine and Anthropometric Status in 6–30 Months Old Indian Children

Abstract: High-quality protein has been associated with child growth; however, the role of the amino acid cysteine remains unclear. The aim was to measure the extent to which plasma total cysteine (tCys) concentration is associated with anthropometric status in children aged 6–30 months living in New Delhi, India. The study was a prospective cohort study including 2102 children. We calculated Z-scores for height-for-age (HAZ), weight-for-height (WHZ), or weight-for-age (WAZ) according to the WHO Child Growth Standards. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A similar study design could be used for active growth life-stages, as was shown recently in 6-12 months stunted Malawian children, that although growth was associated with several serum IAA concentrations, length velocity Z scores were more associated with dispensable amino acids, especially glycine, serine and proline [22]. Similarly in 6-30 months Indian children living in low-middle socioeconomic areas poor growth was associated with low cysteine plasma concentrations [23]. Recently in growing pigs it was shown that supplementing serine and glycine to a low protein diet promoted growth and skin collagen [24 & ] that provides further evidence that indeed, a dietary need could be established with an ideal study design.…”
Section: Serine Glycine and Cysteinementioning
confidence: 82%
“…A similar study design could be used for active growth life-stages, as was shown recently in 6-12 months stunted Malawian children, that although growth was associated with several serum IAA concentrations, length velocity Z scores were more associated with dispensable amino acids, especially glycine, serine and proline [22]. Similarly in 6-30 months Indian children living in low-middle socioeconomic areas poor growth was associated with low cysteine plasma concentrations [23]. Recently in growing pigs it was shown that supplementing serine and glycine to a low protein diet promoted growth and skin collagen [24 & ] that provides further evidence that indeed, a dietary need could be established with an ideal study design.…”
Section: Serine Glycine and Cysteinementioning
confidence: 82%